Revealing the endocrine landscape of INSL3/RXFP2 signaling in hamster - Aidet Ruiz; Luis Ramos (PLoS ONE, 2025)
In mammals, insulin-like peptide 3 (INSL3) and its cognate receptor (RXFP2) are reported to be essential regulators of male reproductive physiology. It is also believed that INSL3/RXFP2 signaling has a role in female ovarian function and follicle development, although its exact mechanisms and functions are still being studied. This research aimed to explore the transcriptional landscape of INSL3/RXFP2 genes in adult hamsters. The cloned cDNA fragments of INSL3/RXFP2 were 888 and 3233 base-pairs (bp), including an open reading frame of 375 bp and 2211 bp, encoding 125 and 737 amino acids, respectively. The phylogenetic relationships, gene function predictions, and three-dimensional structure predictions of INSL3/RXFP2 revealed evolutionary conserved domains. Quantification analysis showed that INSL3 mRNA was highly expressed in the testis, male adrenal glands, and ovary, weakly expressed in male reproductive glands and the female adrenal gland, and barely expressed in the male hypothalamus. INSL3 mRNA expression peaked in ovaries during the proestrus phase, indicating sex-steroid-dependent regulation. RXFP2 mRNA was mainly expressed in the male hypothalamus and uterus, slightly lower in the female cerebellum, epididymis, and ovary, and much lower in the female hypothalamus, male cerebellum, and testis. The RXFP2 in the uterus exhibited the highest expression during the proestrus phase, suggesting regulation via sex steroids. Our findings suggest that sexually dimorphic INSL3/RXFP2 signaling plays a novel role in the reproductive and endocrine systems, particularly in uterine tissue. These results suggest that INSL3/RXFP2 signaling in the hamster model may provide an alternative avenue for studying human female reproduction and endocrine disorders in conditions such as endometriosis or uterine disease in future clinical research.